Assessment of dust concentrations and chemical composition among exposed workers during low-rise building construction - Yaowaret Suanboon; Laksana Laokiat; Pensri Watchalayann; Pongtanawat Khemthong (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Construction processes generate diverse types of dust. This study aimed to specify the concentration of total dust (TD), respirable dust (RD), and particulate matter less than 2.5 (PM2.5) among exposed workers and to identify the chemical composition contained in dust. Methods: A cross-sectional study; TD, RD, and PM2.5 were personally collected among the workers during the low-rise building construction processes according to NIOSH 0500, NIOSH 0600, and EPA-IP-10A, respectively. The concentrations of dust were analyzed by gravimetric method. The element and chemical composition were determined using X-ray diffraction and ICP-OES. One-way ANOVA was used to test the different concentrations of dust. Results: The mean concentrations (GM ± GSD) were 1.43 ± 0.55 mg/m3 of TD, 1.08 ± 0.33 mg/m3 of RD, and 0.84 ± 0.25 mg/m3 of PM2.5. The dust concentrations were not significantly different between sites for TD (p = 0.086), RD (p = 0.124), PM2.5 (p = 0.065), and TD and RD concentrations met the standard regulated by OSHA. The XRD pattern presented peaks of aluminum oxide, calcite, ferric oxide, magnesium oxide, and amorphous silica. Ca was the highest concentration in all dust types, followed by a little of Fe, Al, and Mg, like those found in cement powder. Concrete drilling generated the highest dust concentration, followed by sweep cleaning tasks. Conclusion: Construction workers are exposed to many chemicals in a dusty working environment. Assessing dust concentrations and their physicochemical properties is an imperative tool for improving safety in construction industries.